1998
DOI: 10.1007/bf03161653
|View full text |Cite
|
Sign up to set email alerts
|

Flood and salinity stress of wetland woody species, buttonbush (Cephalanthus occidentalis) and swamp tupelo (Nyssa sylvatica var.biflora)

Abstract: Buttonbush (Cephalanthus occidentalis) and swamp tupelo (Nysxa sylvatica vat. biflora) seedlings were exposed to flooding and salinity conditions simulating the chronic exposure of sea-level rise and the acute exposure of hurricane storm surge. Chronically exposed seedlings were either watered or flooded with 0, 2, or 10 ppt salinity. Those in the acute experiment were watered or flooded with freshwater until exposed to a 21-ppt salinity surge for 48 hours. Freshwater flooding reduced photosynthesis (A), water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…All of the tree species found in the swamps of coastal Louisiana are sensitive to salinity at relatively low concentrations (i.e., 2-7 psu). Most studies investigating the effects of salinity and flooding on tree seedlings also found that there is a negative interaction between salinity and flooding (Conner andAskew, 1992, 1993;McCarron et al, 1998). The flooding estimates used in our analysis were based on stage readings at Pass Manchac, which have been found to be affected by local precipitation but also by the wind-driven circulation of the nearby Gulf of Mexico (Thomson et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…All of the tree species found in the swamps of coastal Louisiana are sensitive to salinity at relatively low concentrations (i.e., 2-7 psu). Most studies investigating the effects of salinity and flooding on tree seedlings also found that there is a negative interaction between salinity and flooding (Conner andAskew, 1992, 1993;McCarron et al, 1998). The flooding estimates used in our analysis were based on stage readings at Pass Manchac, which have been found to be affected by local precipitation but also by the wind-driven circulation of the nearby Gulf of Mexico (Thomson et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…many species, from flood-sensitive crop species (Ashraf and Rehman, 1999;Bradford, 1983) to relatively flood-tolerant wetland ones (Ashraf, 2003;McCarron et al, 1998). However, the net photosynthesis rate at the leaf level could not fully explain the growth at the plant or canopy level; this can be considered a useful, indicative relation in comparative terms (Ehleringer and Field, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Flood depth was maintained at 5 cm over the soil surface. Previous experiments had shown that other woody species could tolerate at least 2 ppt salinity (Conner et al 1997;McCarron et al 1998) and that Taxodium distichum could be naturally found growing in 15.3 ppt water (Allen et al 1994). It was felt that these oak species would not tolerate salt concentrations as high as other species and that they would probably respond very quickly.…”
Section: Methodsmentioning
confidence: 95%